Outcomes associated with antithrombotic strategies in heart failure with reduced ejection fraction and sinus rhythm following acute ischemic stroke - Patel, Parth; Tiongson, Justin; Chen, Austin; Siegal, Taylor; Oak, Solomon; Golla, Akhil; Kamen, Scott; Thon, Jesse M.; Vigilante, Nicholas; Rana, Ameena; Hester, Taryn; Siegler, James E. (Frontiers in Neurology, 2022)
Purpose Insufficient data exist regarding the benefit of long-term antiplatelet vs. anticoagulant therapy in the prevention of recurrent ischemic stroke in patients with ischemic stroke and heart failure with reduced ejection fraction (HFrEF). Therefore, this study aimed to compare longitudinal outcomes associated with antiplatelet vs. anticoagulant use in a cohort of patients with stroke and with an ejection fraction of ≤40%. Methods We retrospectively analyzed single-center registry data (2015–2021) of patients with ischemic stroke, HFrEF, and sinus rhythm. Time to the primary outcome of recurrent ischemic stroke, major bleeding, or death was assessed using the adjusted Cox proportional hazards model and was compared between patients treated using anticoagulation (±antiplatelet) vs. antiplatelet therapy alone after propensity score matching using an intention-to-treat (ITT) approach, with adjustment for residual measurable confounders. Sensitivity analyses included the multivariable Cox proportional hazards model using ITT and as-treated approaches without propensity score matching. Results Of 2,974 screened patients, 217 were included in the secondary analyses, with 130 patients matched according to the propensity score for receiving anticoagulation treatment for the primary analysis, spanning 143 patient-years of follow-up. After propensity score matching, there was no significant association between anticoagulation and the primary outcome [hazard ratio (HR) 1.10, 95% confidence interval (CI): 0.56–2.17]. Non-White race (HR 2.26, 95% CI: 1.16–4.41) and the presence of intracranial occlusion (HR 2.86, 95% CI: 1.40–5.83) were independently associated with the primary outcome, while hypertension was inversely associated (HR 0.42, 95% CI: 0.21–0.84). There remained no significant association between anticoagulation and the primary outcome in sensitivity analyses. Conclusion In HFrEF patients with an acute stroke, there was no difference in outcomes of antithrombotic strategies. While this study was limited by non-randomized treatment allocation, the results support future trials of stroke patients with HFrEF which may randomize patients to anticoagulation or antiplatelet.